Two New Species of the Genus Atrichopogon Kieffer (Diptera: Ceratopogonidae) from Mexico - Huerta, Herón; Dzul, Felipe (Zootaxa, 2012)
Two distinctive new species of the genus Atrichopogon Kieffer from Mexico are described and illustrated based on adults: Atrichopogon pachito, sister species to A. didymothecae Macfie, and Atrichopogon grogani, similar to A. mexicanus Huerta. The two new species Mexican were collected with Malaise traps.